2010
DOI: 10.1007/s11250-010-9763-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Thai indigenous chickens compared with commercial lines

Abstract: A total of 210 chicken samples, from seven strains, were genotyped using 20 microsatellite loci of which 16 are recommended by the Food and Agriculture Organization. The genetic variability and divergence of four Thai indigenous strains and three commercial lines were assessed to generate baseline information for conservation, promotion, and make sustainable utilization of indigenous chicken resources in Thailand. A total of 227 alleles were distributed ranging from six (MCW 111) to 16 (MCW 183 and LEI 166) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
3
10
2
2
Order By: Relevance
“…It showed that trees from functional genes ( Figure 1A) and microsatellites ( Figure 1B) for five fowl populations can be clustered into three groups: CC was split into two groups, egg type (WL) and meat type (BR), while PD represented the same group as RJF. This result is in agreement with functional (calpain gene) polymorphisms of Southeast Asian native chickens (Okumura et al, 2006), and 20 microsatellites that showed that indigenous chickens had spilt from CC (Dorji et al, 2011). A similar conclusion was drawn for Rhode Island Red and Northeast Ethiopian native chickens (Hassen et al, 2009).…”
Section: Phylogenetic Relationshipssupporting
confidence: 83%
See 1 more Smart Citation
“…It showed that trees from functional genes ( Figure 1A) and microsatellites ( Figure 1B) for five fowl populations can be clustered into three groups: CC was split into two groups, egg type (WL) and meat type (BR), while PD represented the same group as RJF. This result is in agreement with functional (calpain gene) polymorphisms of Southeast Asian native chickens (Okumura et al, 2006), and 20 microsatellites that showed that indigenous chickens had spilt from CC (Dorji et al, 2011). A similar conclusion was drawn for Rhode Island Red and Northeast Ethiopian native chickens (Hassen et al, 2009).…”
Section: Phylogenetic Relationshipssupporting
confidence: 83%
“…H E for all functional gene loci was not over than 0.5 because the maximum heterozygosity at a biallelic locus cannot exceed 0.5 (Falconer and Mackay, 1996). The H E for all microsatellite loci in Gallus spp was greater than 0.5, which was in agreement with Dorji et al (2011). (Table 3) may lead to positive assortment or a situation of high homozygosity.…”
Section: Genetic Diversitysupporting
confidence: 83%
“…These chickens were developed from four generations of inter se mating between Thai native chickens, known as Chee (sire line) (Dorji et al, 2011), crossed with exotic commercial layers (dam line). Breeding was conducted at the Research and Development Network Center for Animal Breeding (Native Chicken), Khon Kaen University, Thailand.…”
Section: Chicken Populations and Traitsmentioning
confidence: 99%
“…The meat quality of these indigenous chickens has a unique taste with favorable toughness and hence, offering a low cholesterol and fat meat product [10]. Although there were several attempts to characterize these chickens using their physical properties and the successive proteomic profiling of the meat [9,11-13], only few research efforts have undertaken a genetic characterization of these indigenous chickens [4,14-17]. Up to the present, the genetic structure of Thai indigenous chickens remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers of chickens have previously been reported [5,6,14,15,18-20]. However, the limited number of these microsatellites may not capture the underlying genetic differences among closely related breeds.…”
Section: Introductionmentioning
confidence: 99%